Information Asymmetry, Institutional Ownership, Related Party Transactions and The Board Size to Real Earnings Management - Ivander Yunus; Paulina Sutrisno (Global Financial Accounting Journal, 2022)
Purpose – The purpose of this study is to examine the relationship between information asymmetry, institutional ownership, related party transactions and the board size on real earnings management. This research was conducted because there are still inconsistencies in the results of previous studies. Research Method – This study uses a sample of manufacturing companies listed on the IDX (Indonesia Stock Exchange) in the period 2018-2020. The sample in this study was obtained using purposive sampling method. There are 213 data that meet the sample selection criteria. As for testing the hypothesis of this study using multiple regression analysis. Findings – The results of this study indicate that information asymmetry, institutional ownership and related party transactions have a positive effect on real earnings management. Meanwhile, the board size has no relationship to real earnings management. Implication – The implication of this research is to provide additional perspective on the positive effect of information asymmetry, institutional ownership and (RPT) related party transactions on real earnings management. The high level of information asymmetry, institutional ownership and related party transactions will encourage real earnings management. In addition, the implications of this study for financial statements user, especially to decisions making for investors, are to pay attention to and consider factors that can affect real earnings management such as the high level of information asymmetry, institutional ownership and the related party transactions size.